Magnetorheological Fluids Examination for Antivibration Mounts at Impact Loads. (2016) - Gordeev, B.A.; Dar'enkov, A.B.; Okhulkov, S.N.; Plekhov, A.S.
Abstract: In this work the question of magnetorheological fluids usage in damping systems of electromechanical power installations and machinery are studied. The physical backgrounds of magnetic fluids characteristics operation with respect to inner magnetic fields are considered. The processes appearing in magnetorheological fluids at impact loads are looked into. These tasks are solved within the frame of magnetorheological fluid only due to the fact that electromagnetic impulses appear on solenoid windings which are meant to create an inner control magnetic field. The amplitude and the impulses duration is an impact load function. Their influence is to be taken into account when developing magnetorheological dampers.